Genome-Wide Identification of Rare and Common Variants Driving Triglyceride Levels in a Nevada Population - Read, Robert W.; Schlauch, Karen A.; Lombardi, Vincent C.; Cirulli, Elizabeth T.; Washington, Nicole L.; Lu, James T.; Grzymski, Joseph J. (Frontiers in Genetics, 2021)
Clinical consequences of elevated triglyceride levels are well-known: coronary heart disease, hypertension, and diabetes. Underlying genetic and phenotypic mechanisms are not fully understood, partially due to lack of coordinated genotypic-phenotypic data. Here we use the Healthy Nevada Project, a population of 10,316 sequenced participants with longitudinal electronic health records, to examine consequences of altered triglyceride levels. Specifically, Healthy Nevada Project participants sequenced by the Helix Exome+ platform were cross-referenced to their electronic medical records to identify: 1) rare and common single-variant genome-wide associations; 2) gene-based associations using a Sequence Kernel Association Test; 3) phenome-wide associations with triglyceride levels; and 4) pleiotropic variants linked to triglyceride levels. The study identified 594 significant single-variant associations (p < 6.0 x 10-9), many in chromosome 11’s triglyceride hotspot: ZPR1, BUD13, APOC3, APOA5. A well-known protective loss-of-function variant in APOC3 (R19X) was associated with a 49% decrease in triglyceride levels in the cohort. Seventeen gene-based triglyceride associations were identified; five of these genes surprisingly did not include a single variant with significant associations. Results at the variant and gene level were validated with the UK Biobank. The combination of a single-variant genome-wide association, a gene-based association method, and phenome wide-association studies identified rare and common variants, genes, and phenotypes associated with elevated triglyceride levels, some of which may have been overlooked with standard approaches.